2011
DOI: 10.1002/er.1701
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relative efficiency of energy use among similar manufacturing industries

Abstract: This article presents a methodology to measure relative industrial energy efficiency across plants within a manufacturing sector through the use of energy-production signatures (EPSs). Linear programming in combination with regression methods, benchmarking and simulation models are used to study the behavior of a representative manufacturing plant. The methodology is validated using data available from the Department of Energy database. The proposed EPSs can be used for proactive benchmarking and diagnostic pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Feng and Joung [44] proposed a sustainable manufacturing measurement infrastructure and Tanaka [45] explored different ways to measure energy efficiency performance. Additionally, Aguirre et al [46] proposed metrics called 'energy-production signatures' for diagnosis of energy inefficiencies and benchmarking of energy-related performances of manufacturing plants. Later, Zhou et al [47] developed an approach for monitoring energy efficiency trends over time in a country and for comparing the economy-wide energy efficiency performance among countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feng and Joung [44] proposed a sustainable manufacturing measurement infrastructure and Tanaka [45] explored different ways to measure energy efficiency performance. Additionally, Aguirre et al [46] proposed metrics called 'energy-production signatures' for diagnosis of energy inefficiencies and benchmarking of energy-related performances of manufacturing plants. Later, Zhou et al [47] developed an approach for monitoring energy efficiency trends over time in a country and for comparing the economy-wide energy efficiency performance among countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Less aggregated benchmarking for manufacturers of aluminium was carried out by Aguirre et al (2010), where an energy-production signature was used. Other studies, such as Boyd (2016), Oh and Hildreth (2014) and Blomberg et al (2012), also adopt a site-level benchmarking approach.…”
Section: Benchmarking Energy Efficiencymentioning
confidence: 99%
“…In order to better understand the energy efficiency in the manufacturing sector, plant-level energy efficiency analysis has received great attention from researchers and engineers [4][5][6][7][8][9]. However, because of the lack of systematic data collection and limited analytics in the manufacturing industry, it has been rare that comprehensive studies of energy efficiency are reported in the literature.…”
Section: Needs and Objectivesmentioning
confidence: 99%